Analisis Jumlah Bakteri Dan Uji Organoleptik Pada Abon Ikan Cakalang (Katsuwonus pelamis) Di Kota Gorontalo - Bakari, Hijrah; Adipu, Yulianty (Universitas Gorontalo, 2019)
Abon fish is a dried food made from suiran-suiran meat and spices. Ingredients boiled or steamed, then disuir, mixed with spices and fried until cooked into abon. The purpose of this study was to find out the number of bacteria and the quality deterioration in skipjack tuna (Katsuwonus pelamis) sold in Super Market or SME in Gorontalo City. This research used purposive sampling method with Total Plate Count Test (ALT) and Organoleptic Test. Samples of skipjack tuna (Katsuwonus pelamis) were taken to determine the total number of bacteria by using the pour plate method. The results showed that 15 fish abon samples with the highest number of bacterial colonies were 220,000 cow / gr fish samples abon 9 with the number of bacterial colonies of 91,000 cc / g and 13 fish abon samples with the number of bacterial colonies of 31,000 cc / g. Whereas in the Hedonic Test method the average panelist in the color hedonic test judgment likes sample 6 with an average rating of 4.04, the panelist sense of hedonic test likes the sample 1 with an average rating of 4.08, the panelist panelic hedonic test likes sample 1 with an average grade of 3.92 and a panelist texture hedonic test favored sample 12 with an average grade of 3.68. Hedonic test analysis showed that the amount of bacteria in skull tuna abon have an effect on to decrease of quality and level of panelist preferences